The role of evaluating inspiratory constraints and ventilatory inefficiency in the investigation of dyspnea of unclear etiology - Neder, J. Alberto; Berton, Danilo C.; Marillier, Mathieu; Bernard, Anne-Catherine; O.Donnell, Denis E. (Respiratory medicine, 2019)
Exertional dyspnea increases when the mechanical output of the respiratory muscles becomes uncoupled from increases in neural respiratory drive. Combining measurements of inspiratory constraints and ventilatory inefficiency may better uncover the role of mechanical-ventilatory abnormalities on exertional dyspnea than the currently-recommended approach, i.e., a low breathing reserve. We determined the presence of a low breathing reserve (1-(peak ventilation (V̇E)/estimated maximal voluntary ventilation) x 100 < 15%), critical inspiratory constraints (tidal volume (VT)/exercise inspiratory capacity (ICdyn) > 0.7) and ventilatory inefficiency (V̇E/CO2 output (V̇CO2) nadir>34) in 284 subjects (161 males) with “disproportionate dyspnea” (N = 148), “dyspnea with multiple potential causes” (N = 93) and “dyspnea without an apparent cause. The agreement between breathing reserve and assessment of inspiratory constraints was only “fair” (kappa [confidence interval (CI)] = 0.264 [0.169–0.358]). Attainment of critical inspiratory constraints and an upward inflection in dyspnea ratings systematically preceded a low breathing reserve. Of note, ~55% (93/167) of subjects with normal breathing reserve showed critical inspiratory constraints despite largely preserved lung function. Regardless of the breathing reserve, subjects showing critical inspiratory constraints and/or poor ventilatory efficiency reported higher dyspnea and more impaired exercise tolerance compared to their counterparts (p < 0.05). Poor ventilatory efficiency strongly predicted a high dyspnea/work rate in subjects without critical inspiratory constraints regardless of the breathing reserve (odds ratio [95% CI] = 4.21 [2.01–6.42; p < 0.001). An integrated analysis of inspiratory constraints and ventilatory inefficiency is key to uncover physiological abnormalities germane to dyspnea in clinical populations in whom the origins of this distressing symptom are uncertain. •~55% of subjects with dyspnea of unclear origin showed inspiratory constraints.•These subjects, however, had normal breathing reserve.•Inspiratory constraints plus ventilatory inefficiency predicted dyspnea burden and exercise intolerance.•These measurements should be routinely used in the assessment of dyspnea of unclear origin.